English teachers’ problems in designing lesson plans at SMPN 2 Gudo: Teachers’ perception - Fatmaliana, Dian; Zuhriyah, Mukminatus (Universitas Sarjanawiyata Tamansiswa, 2022)
One of the main tasks for a teacher is to make lesson plans before carrying out the teaching process in the class. The use of lesson plans is quite effective in improving the quality of learning. But nowadays, many teachers do not make lesson plans. They copy and paste from the internet or use templates from other teachers. The purposes of this research are to describe the perception of English teachers, the obstacles with the solutions, and the suitability of the English lesson plan components at SMPN 2 Gudo. The researcher used a descriptive qualitative method. The research subjects were 2 English teachers at SMPN 2 Gudo. The researcher used 2 data collection techniques, namely: interview and documentation. The results from this study show that the perception of English teachers was the care and awareness of the lesson plan, the English teacher faced difficulties not in designing the lesson plan but in implementing it in the class, and there are still discrepancies between the components that have been made by the teacher, in part of the operational verb and the writing of learning media. This research is expected to provide benefits for students of the faculty of education and teachers so that they can improve their ability to develop lesson plans better.